MAKNA KEKERASAN FISIK DALAM FILM MOTHER KARYA TATSUSHI OUMORI - Maretya, Gex Nitya Dwi; Ni Wayan Meidariani; Anak Agung Dian Andriyani (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2022)
This study aims to determine the meaning of physical violence on the characters Shuuhei and Akiko in the film Mother. The theory used in this research is Charles Sanders Peirce's semiotic theory of icons, indexes and symbols. The method used is descriptive qualitative method. Methods and techniques of data collection in this study using the method of listening to the advanced technique of note-taking. Presentation of data analysis using informal methods presented in ordinary words. The results of this study indicate that there are signs of physical violence on the characters of Akiko and Shuuhei in the form of punches, body throws, stampedes, grabs, slaps, drags, and kicks. The meanings of physical violence are (1) Ryou's angry expression towards Shuuhei, (2) emotional expression and hurt towards a partner that is vented to a child, (3) Kaede's angry expression towards Akiko for using Shuuhei, and (4) venting jealousy towards partner.